(3Pjd fRgI GdMOGFb aj cjajI UfYI GdGdI GdeSeGI HWHb GdefGWbs - (3nLreTpjO Hf eSYhO Hf eMehO Hf eMeO GdcGTGfj, ZjGK GdOjf , J (B832 (3g` s; (3LeTjO Hf SYhO , LeTjO Hf eSYhO Hf eMehO Hf eMehO GdcGTGfj, ZjGK GdOjf,J (B832 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO aEf CMhL Ndb Gddg JYGdi GdGdMGb GdChd hgh Cf efWbI GdbeQ jecf Cf fQSegG s
(3BNQgG (B:s
(3GdGdMGb GdYGTQ ai McGjI JSejI GdBdg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GfXQI eY fRgI GdMOGFb ai faS GdHYKI HQbe (B346s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B136 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B158s
Keywords: (3Gdadcs